Analisis Peran Human Resource Dalam Proses Rekrutmen Karyawan Pada Salah Satu Perusahaan Logistik Berbasis Teknologi di Jakarta - Anggraini Nurcahya Permata; Christian Wiradendi Wolor (Kampus Akademik Publiser, 2026)
Abstract. Recruitment is one of the most important activities in acquiring human resources that meet organizational needs. In its implementation, Human Resources plays a strategic role in ensuring the effectiveness of the recruitment process and selecting candidates whose competencies and characteristics align with the organization's culture. This study aims to analyse the role of Human Resources in the employee recruitment process and identify the challenges encountered during recruitment activities at Company X. This study employed a descriptive qualitative approach using interviews, questionnaires, documentation, and literature review as data collection techniques. The primary informant was a Human Resources staff member directly involved in the recruitment process. Supporting data were obtained from 15 respondents who had experience participating in job or internship recruitment processes, as well as follow-up interviews with two selected respondents. Data were analysed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that Human Resources plays a role in every stage of recruitment, including workforce planning, candidate sourcing, candidate screening, interviewing, offering, and onboarding processes. The study also found that limited employer branding remains one of the main challenges in attracting potential candidates. To address this issue, Human Resources applies a more personalized approach, utilizes digital recruitment platforms, and maintains active communication throughout the recruitment process. Therefore, Human Resources plays a crucial role in supporting recruitment effectiveness and successful employee hiring at Company X.